Market access, teff production, and fertilizer use over time - Kedir Jemal, Mekamu; Schmidt, Emily; Tilahun, Helina (International Food Policy Research Institute, 2018)
This chapter aims to provide a spatial interpretation of teff production while exploring changes in infrastructure and agricultural inputs over time. Geographic overlap between transportation investments, fertilizer application, and increases in teff production provide a qualitative assessment of how road expansion, agricultural production, and agricultural inputs have changed over time in more remote areas of Ethiopia. The study covered in this chapter uses a rich set of data on agricultural indicators collected by Ethiopia’s Central Statistical Agency (CSA) as well as Geographic Information Systems (GIS) data on roads, agroecologies, and other biophysical information to analyze the transformation of teff production patterns in Ethiopia since 1997. The remainder of the chapter is as follows. The first section provides an overview of teff production in Ethiopia as well as a brief literature review of previous studies that examined the overlap of agricultural potential with regards to infrastructure development. The next section describes the data and methodology used to explore teff production, fertilizer application, and infrastructure development over time. The chapter then discusses the spatial heterogeneity of teff production patterns over time taking into account agroecological conditions, transportation infrastructure, and market access. Fertilizer application trends on teff production over time and links to major markets within the country are explored before the chapter ends with a conclusion.